ANALISIS NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR ( Study Empiris 4 Perusahaan Yang Terdaftar di BEI ) - Amdan Firmansyah Hadqia; Nira Aktaviani; Dinda Apriliani (Universitas Nusa Putra, 2021)
Purpose: This study aims to provide information and determine the development of the manufacturing industry which dominates the companies listed on the Indonesia Stock Exchange (IDX), in this case, specifically to determine the value of companies in the Basic Industry Sector and chemical in the Animal Feed Sub-Sector. Methods: In measuring Firm Value, you can use Price Earning Ratio (PER), Price to Book Value Ratio (PVB) and Tobin’s Q Ratio, but in this study we use the Tobin’s Q ratio because it is easy to understand both from our side of the researcher as well as from the side. reader. Data Analysis: This study used 4 animal feed sub-sector companies listed on the Indonesia Stock Exchange (BEI) 2015-2018 with information that can be accessed on the official website www.idx.com. Results and Discussion: The results of this study indicate that there are still companies that have company value below one or are categorized as undervalued in a certain year, there are also companies that show a company value above 1, which means that the company has the potential to develop. Conclusion: The basic industry and chemical sector have one of the animal feed subsectors, in which there are 4 companies. In our analysis, we use Tobin's Q, which counts in 4 years, namely 2015-2018 getting results more than 1, but there are some years that get less than 1.